Study of MSMEs Performance: Factors Affecting MSMEs Performance through Marketing Adoption with Social Media - Lim, Desmond; Kesumahati, Erilia (JURNAL ADMINISTRASI & MANAJEMEN, 2023)
Technology has been growing rapidly recently. The close relationship and dependence between humans and social media, becomes an opportunity for companies to market their products through social media. This article discusses some of the things that influence companies to adopt social media as a company marketing tool. Some of these variables include the context of technology, organization, environment, perceived usefulness and perceived ease of use of social media, and attitudes towards technology and the ability to control technology. This study targets MSME players who sell imported products in the Riau Islands Province. The analysis was carried out by testing data from 200 respondents collected responses through Google Forms and data tested with the SEM-PLS model through the help of the SmartPLS application. It is known that the variables of technological context and environmental context have a significant positive relationship to the adoption of social media as a marketing tool. The environmental context also has a positive significant influence on the increasing performance of companies that use social media in marketing. Meanwhile, the adoption of social media in marketing is known to have a significant positive effect on improving company performance.